2016
DOI: 10.4103/1305-7456.195158
|View full text |Cite
|
Sign up to set email alerts
|

Dentists’ knowledge and practice regarding prevention of infective endocarditis

Abstract: Objectives:The objective of this study is to assess the knowledge and practice of dentists from Jordan, regarding prevention of infective endocarditis (IE) in dental practice.Materials and Methods:A sample of Jordanian dentists was interviewed regarding their IE knowledge and practice using a validated and pretested survey instrument.Results:Most of the dentists have encountered a patient with IE who needed prophylactic antibiotic (PA) and have prescribed antibiotics to prevent IE. Jordanian dentists’ approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…The most frequently reported invasive, bacteremiacausing dental procedures were exodontia and dental implant, which is in line with previous studies [12,14,17,18,20]. The seven correct response alternatives in this question were frequently selected, similarly to what was previously described for heart conditions.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The most frequently reported invasive, bacteremiacausing dental procedures were exodontia and dental implant, which is in line with previous studies [12,14,17,18,20]. The seven correct response alternatives in this question were frequently selected, similarly to what was previously described for heart conditions.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies have analyzed the knowledge of dentists and / or dental students about the topic and demonstrated a limited knowledge and the existence of many questions [5,12]. Common mistakes include the choice for the antibiotic and its correct dosage as well as lack of knowledge on conditions that do not pose a high risk to the patient, e.g., non-invasive dental procedures that cause bacteremia [13][14][15][16][17][18]. It was also shown that a pedagogic intervention (e.g., informative talk) can effectively improve the frequency of correct responses [19].…”
Section: Introductionmentioning
confidence: 99%
“…The British Society for Antimicrobial Chemotherapy has recommended antibiotic prophylaxis before dental procedures exclusively for patients with a history of previous IE infection or with cardiac valve replacement (24). Another study conducted by Ryalat et al, reported that 87% of Jordanian dentists recommended antibiotic prophylaxis in patients with prosthetic devices (25). In this study, the vast majority of the study population was aware of the general cardiac indications for antibiotic prophylaxis toward the prevention of IE.…”
Section: Discussionmentioning
confidence: 74%
“…The study conducted by Ryalat et al, observed that amoxicillin was the preferred choice of the antibiotic drug among dentists to prevent IE, followed by clindamycin (17.3%), and a minority of the dental population preferred metronidazole, lincomycin, gentamycin, or clarithromycin (25). It was also the drug of choice among Nigerian dentist with 89% preferring it, however, Japanese dentists preferred cephams followed by penicillin drugs (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…57.5% 89%. 4,7,16,20 The administering prophylactic antibiotics at the correct time during the preoperative period for dental procedures that produce significant bacteremia. She emphasized that it is essential that prophylactic antibiotics should be administered shortly before the dental procedure.…”
Section: Discussionmentioning
confidence: 99%